2016
DOI: 10.1007/s00595-016-1388-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of urapidil on testicular torsion–detorsion injury in rats

Abstract: The administration of urapidil before detorsion prevents ischemia/reperfusion cellular damage in testicular tissue. LMWH was not found to have a beneficial effect on testicular T/D injury in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
6
20
0
1
Order By: Relevance
“…Also, in a study on effect of intraperitoneal injection of the Nifedipine (100 mg/kg) on testicular torsion-detorsion injury in rats, Mestrovic et al 34 reported Nifedipine significantly decreased MDA and increased SOD and GPx levels which our results was in agreement to this report. On protective effect of Urapidil on testicular torsion Meštrovic´ et al 35 reported intraperitoneal injection of the 10 ml/kg of the Urapidil 30 min before detorsion significantly significantly decreased MDA and increased SOD and GPx levels on testicular torsion-detorsion injury in rats. Also, Ozbek et al 36 revealed intraperitoneal injection of the Apocynin (20 mg/kg) significantly increased SOD, GPx and CAT and decreased MDA levels in 4h torsion followed by 1h detorsion rats.…”
mentioning
confidence: 99%
“…Also, in a study on effect of intraperitoneal injection of the Nifedipine (100 mg/kg) on testicular torsion-detorsion injury in rats, Mestrovic et al 34 reported Nifedipine significantly decreased MDA and increased SOD and GPx levels which our results was in agreement to this report. On protective effect of Urapidil on testicular torsion Meštrovic´ et al 35 reported intraperitoneal injection of the 10 ml/kg of the Urapidil 30 min before detorsion significantly significantly decreased MDA and increased SOD and GPx levels on testicular torsion-detorsion injury in rats. Also, Ozbek et al 36 revealed intraperitoneal injection of the Apocynin (20 mg/kg) significantly increased SOD, GPx and CAT and decreased MDA levels in 4h torsion followed by 1h detorsion rats.…”
mentioning
confidence: 99%
“…In an experimental study conducted by Mestrovic J. et al, the rats treated with nifedipine had a significant decrease in malondialdehyde level and apoptosis and had significant increases in superoxide dismutase and glutathione peroxidase activities in ipsilateral testes compared with those not treated with nifedipin (Mestrovic, 2014). Also in another study, Meštrović et al (2017) shown protective effect of urapidil on testicular torsion-detorsion injury in rats.…”
Section: Xue Et Al Investigated the Effect Of Gradual Low-flow Repermentioning
confidence: 82%
“…In another study, IMA level was significantly higher in both the 2-hr acute torsion and 2-month chronic torsion groups, and it was stated that IMA level might have a predictive value for fertility in addition to its use in the diagnosis of testicular torsion (Mentese et al, 2012). Also in another study, Meštrović et al (2017) shown protective effect of urapidil on testicular torsion-detorsion injury in rats. Pre-orchiectomy IMA levels were significantly higher in the sham group than in the other groups.…”
Section: Xue Et Al Investigated the Effect Of Gradual Low-flow Repermentioning
confidence: 90%
“…Diclofenac, an anti-inflammatory agent, exerted similar effects, as evidenced by elevated levels of DNA fragments detected using the TUNEL assay to measure the levels of germ-cell apoptosis (Mogilner et al, 2006). Bozlu et al (2009) When given before the detorsion, Nifedipine, a calcium channel blocker vasodilator and Urapidil, a α1-adrenoceptor antagonist sympatholytic prevented I/R damage in the testicular tissue cells (Meštrović et al, 2014(Meštrović et al, , 2017. Furthermore, apocynin, an NADPH oxidase inhibitor, reduced the degree of lipid peroxidation, induced the formation of antioxidant substances, and reversed the I/R injury in the rat testis cells (Ozbek et al, 2015;Şener et al, 2015).…”
Section: Caspase-3 Normally Exists In the Cytosolic Fraction Of Cells Asmentioning
confidence: 98%
“…Antioxidants such as N-acetylcysteine (Cay et al, 2006) and garlic extract (Unsal et al, 2006) have been used to lower the amounts of overgenerated ROS. Bozlu et al (2009) When given before the detorsion, Nifedipine, a calcium channel blocker vasodilator and Urapidil, a α1-adrenoceptor antagonist sympatholytic prevented I/R damage in the testicular tissue cells (Meštrović et al, 2014(Meštrović et al, , 2017. Diclofenac, an anti-inflammatory agent, exerted similar effects, as evidenced by elevated levels of DNA fragments detected using the TUNEL assay to measure the levels of germ-cell apoptosis (Mogilner et al, 2006).…”
Section: Caspase-3 Normally Exists In the Cytosolic Fraction Of Cells Asmentioning
confidence: 99%